Optimization of reversed-phase conditions for separation of serotonin receptor ligands in liquid chromatography - Obradović, Darija; Savić, Jelena; Joksimović, Jovana; Marković, Bojan; Vujić, Zorica (Archives of Pharmacy, 2022)
The serotonin receptor ligands, such as structurally related arylpiperazine and benzothiazepine derivatives, are most commonly used in the treatment of schizophrenia, depression, and manic disorders. Due to emphasized lipophilicity, their retention can be successfully defined under the reversed-phase (RP) chromatographic conditions. Using the experimental design methodology, the retention of selected serotonin receptor ligands (aripiprazole, ziprasidone, risperidone, olanzapine, quetiapine, mirtazapine) was tested on RP stationary phases, in order to define differences in their retention mechanisms and ensure the further optimization of separation conditions. The silica modified, C8 and pentafluorophenylpropyl (PFP) columns were used as stationary phases, while the mobile phase was a mixture of acetonitrile and ammonium acetate. The experimental plan was defined according to the central composite design varying the following factors: ammonium acetate concentration (15-25 mM), volume fraction of acetonitrile (40-50% v/v), and column temperature (20-30℃). The differences between retention on C8 and PFP columns were presented by using the radar plots and principal component analysis. The obtained differences are especially visible in the case of ziprasidone, olanzapine, quetiapine and mirtazapine, which may explain the occurrence of inversions in their elution order. On C8 phase the separation of structurally related arylpiperazine or benzothiazepine derivatives was achieved, while the PFP phase showed more successful applicability in the separation of all tested ligands. The slightly higher values of the selectivity parameter were obtained for 40% of acetonitrile in the mobile phase. In further optimization of the separation conditions, the PFP bonded stationary phase can be successfully applied.